Brazilian soap opera and American TV series: narrativity according Barthes - Merenciano, Levi Henrique (Open Science Journal, 2021)
Abstract: This paper aims to compare two audiovisual tv products: a Brazilian soap opera “Avenida Brasil” (Brazil Avenue, 2012) and an American TV series Grey´s Anatomy (2005). The theoretical and methodological approach are structural narratology studies and French Semiotics, based on narratology studies influenced by Propp, Greimas and Barthes. The main goal is to analyze and compare the narrative structure of the first episodes of both TV productions by means the cardinal and catalyzer functions according to Roland Barthes narratives point of view. Keywords: brazilian soap opera, tv series, structural narratology, semiotics